Prostitution and (il)legal migration as possible hidden forms of trafficking in human beings: The analyses of the practice of the Magistrate Court in Belgrade - Anđelković Marija (Temida)
In this paper the author analyses all the cases from the 2002 practice of Magistrate Court in Belgrade, which relate to prostitution and illegal migration. The main aim of this paper is to show who are the women and men who are accused and punished for prostitution and illegal migration, as well as to argue that the part of them are in fact victims of trafficking in human beings. In conclusion, the author suggests the necessity for training of magistrate judges in order to be able to recognize victims of trafficking and, consequently, to be able to treat them as victims rather than as offenders.